ANALISIS SWOT KONSEP DASAR FILSAFAT IDEALISME IMPLIKASI DAN APLIKASI DALAM PENDIDIKAN - I Gusti Ayu Suasthi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
Idealism is a school of philosophy that has existed since the fourth century developed by Plato as a philosopher from Athens / Greece who lived in the year 427-347 BC. This philosophy of idealism is generally referred to as the philosophy of the 19th century. Plato with his view emphasizes the importance of the superiority of mind (mind), spirit (soul) or spirit (spirit) rather than material things. in the senses is a mere appearance, the real reality is the ideas or forms of origin of the apparition. Ideas are an “eternal Universal” world. Hamdani Ali describes that: Plato concludes that there is an apparent reversed value and that value is much more important because the invisible is something metaphysical and continues to exist, that is ideas.